Tourism in the Arab World An Industry Perspective - Almuhrzi, Hamed; Alriyami, Hafidh; Scott, Noel (Multilingual Matters, 2017)
This book is the first to explore Arabic tourism from a business viewpoint, rather than taking a sociological, anthropological or political stance. It focuses on business planning, management and marketing destinations in the Arab World, which are topics crucial for industry stakeholders and which have previously been neglected in the tourism literature. The book examines similarities and differences in the emergence and development of the tourism industry in countries across the Arab world as well as its inbound and outbound travel flows. It analyses several different aspects of Arabic tourism including tourism policy, organisation and planning, tourism product development, destination marketing and consumer behaviour. This volume will be of interest to postgraduate students and researchers of tourism studies, business and Middle Eastern studies
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Jan 2020)
Keywords: Arab world; Arab; Middle East; business; tourism industry; tourism management; tourism; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism; Tourismus; Arabische Staaten; Aufsatzsammlung